P149 Characteristic And Prognosis Of Patients With Copd And Type 2 Respiratory Failure. (10th November 2014) - Spruell, T; Dave, C; Mukherjee, R; Turner, AM
Abstract : Introduction: Factors associated with type 2 respiratory failure (T2RF) in COPD have been poorly described. Co-existent obstructive sleep apnoea is thought to play a part, 1 and episodes of worsening hypercapnia, associated with acidosis (AHRF), at the time of exacerbations is a well recognised feature. 2 We hypothesised that the development of hypercapnia or type 2 respiratory failure would associate with a higher risk of subsequent AHRF and higher mortality. Methods: 292 patients who had been prescribed oxygen for their COPD during 2006–2010 were studied. Medical records were reviewed for lung function, blood gases in the stable state, episodes of AHRF and mortality up to the end of March 2014. Cross-sectional analyses seeking associations of hypercapnia and T2RF were carried out, together with comparisons of FEV1 decline, AHRF and mortality between those with and without T2RF. Results: Mean follow up duration was 6.7 years. 164 patients died and 90 had one or more episodes of AHRF; AHRF was more common in T2RF (p = 0.046). Cox regression analysis, adjusting for age, demonstrated that death was more likely in those with T2RF compared to T1RF (Figure 1 ; p = 0.018). A rise in CO2 after administration of oxygen during the test of LTOT eligibility showed a similar association, but it was less strong (p = 0.041). Lung function was strongly associated with T2RF and subsequent use of NIV for AHRF; 53% of those with FEV1 <30% predicted eventually required it. This increased to 81% if FEV1 was less than 20% predicted. After adjusting for baseline FEV1 in the regression model, FEV1 decline did not differ between T2RF and T1RF. Conclusions: LTOT patients with T2RF are at higher risk of AHRF and death, thus should be followed up more closely and more effort made to record advance wishes regarding NIV, if appropriate. References: Obesity and respiratory diseases. Murugan AT, Sharma G. Chron Respir Dis . 2008; 5(4):233–42 Acidosis, non-invasive ventilation and mortality in hospitalised COPD exacerbation. Roberts CM, Stone RA, Buckingham RJ, Pursey NA, Lowe D. Thorax (2011) 66(1): 43–8